Osteology and phylogenetic relationships of Tehuelchesaurus benitezii (Dinosauria, Sauropoda) from the Upper Jurassic of Patagonia - Carballido, José Luis (2011)
The diversification and early evolution of neosauropod dinosaurs is mainly recorded from the Upper Jurassic of North America, Europe, and Africa. Our understanding of this evolutionary stage is far from complete, especially in the Southern Hemisphere. A partial skeleton of a large sauropod from the Upper Jurassic Cañadón Calcáreo Formation of Patagonia was originally described as a 'cetiosaurid' under the name Tehuelchesaurus benitezii. The specimen is here redescribed in detail and the evidence presented indicates that this taxon is indeed a neosauropod, thus representing one of the oldest records of this clade in South America. A complete preparation of the type specimen and detailed analysis of its osteology revealed a great number of features of phylogenetic significance, such as fully opisthocoelous dorsal vertebrae, the persistence of true pleurocoels up to the first sacral vertebra, associated with large camerae in the centrum and supraneural camerae, and an elaborate neural arch lamination, including two apomorphic laminae in the infradiapophyseal fossa. The phylogenetic relationships of this taxon are tested through an extensive cladistic analysis that recovers Tehuelchesaurus as a non-titanosauriform camarasauromorph, deeply nested within Neosauropoda. Camarasauromorph sauropods were widely distributed in the Late Jurassic, indicating a rapid evolution and diversification of the group. © 2011 The Linnean Society of London.